Electrochemical Characteristics of Pyrolytic Carbon Coated Silicon for Anode Materials of Lithium Ion Batteries - Kim, Jung Sub; Byun, Dongjin; Lee, Haw Young; Lee, Joong Kee (AMER SCIENTIFIC PUBLISHERS, 2015)
Pyrolytic carbon coated silicon is prepared and employ it as an anode material for lithium secondary batteries. The pyrolytic carbon coating of silicon with sucrose precursor not only provides a suitable carbon matrix but also suppresses the breaking away of Si from the current collector during the insertion and extraction of Li+. The increase of disordered carbon content leads to the increase of discharge capacity retention. The improvements of cycle stability are attributed to a decrease in the volume change of the silicon, good networking between Si particles, and good adhesion of the current collector with the active material. The nano Si combined with the disordered carbon leads to an increase of capacity retention and initial coulombic efficiency.
Keywords: THIN-FILMS; PERFORMANCE